A reliable microplate assay for determination of B-galactosidase activity in Neurospora crassa strains bearing lacZ fusions - Kwangwon Lee; Daniel J. Ebbole (Fungal Genetics Reports, 1996)
We have been using lacZ as a reporter gene in N. crassa. The standard -galactosidase assay can be labor intensive and time consuming when large numbers of strains are assayed simultaneously. We sought a technique to simplify the pipetting steps involved in assay preparation and in optical density reading. High reproducibility and rapid processing was obtained by adapting the standard test tube method to a microassay performed in a 96-well microplate.